Professional Adjustment and its Relationship to Psychoso - ghadri, ibrahim; zegar, fathi (Journal of Social Sciences and Humanities, 2023)
The current study aims to reveal the nature of the relationship between Professional Adjustment and Psychosomatik symptoms with teachers of Primary Education, as well as knowing the diffrences between the two genders in both; Professional Adjustment and Psychosomatik symptoms among members of the study sample. To achieve this, we have applied the Professional Adjustment scale prepared by the researcher, and the Psychosomatik symptoms scale prepared by Ali hassen (2008) on a sample of 198 male and female teachers who were randomly selected. Based on the nature of the study, the descriptive approchwas used. After the statistical treatment, the study concluded that there is a statistically significant correlation inverse relationship between each of the Professional Adjustment and Psychosomatik symptoms among the teachers of Primapry Education in M’sila. It also found that there are no statistically significant differences between the two genders in both; Professional Adjustment and Psychosomatik symptoms.